Cutaneous Pigmented Neurofibroma in a Pig – Morphology and Immunohistochemical Profile. (April 2019) - Becker, K.; Kegler, K.; von Altrock, A.; Kuchelmeister, K.; Baumgärtner, W.; Wohlsein, P.
Summary: Peripheral nerve sheath tumours are rare in pigs. In the present case, a juvenile female hybrid pig showed a solitary, pigmented, cutaneous mass. Histologically, it consisted of clustered melanin-laden, epithelioid cells as well as spindle cells forming bundles and nodules. The latter were surrounded by perineurial-like cells. Single Wagner–Meissner-like corpuscles were present. Immunohistochemically, the epithelioid cells expressed S100 protein, melan A and the p75 neurotrophin receptor (p75 NTR ). The spindle cells expressed S100, sex determining region Y-box 2, p75 NTR, Krox20, growth associated protein 43 and glial fibrillary acidic protein. Perineurial-like cells were positive for p75 NTR, α-smooth muscle actin and cytokeratin. Taken together, the histological und immunohistochemical findings support the diagnosis of a cutaneous pigmented neurofibroma.